The Influence of Leadership and Motivation on Employee Performance at the South Tangerang Fire and Rescue Service - Laila Irawati (Pendidikan Administrasi Perkantoran, Universitas Negeri Makassar, 2020)
Human resources (HR) is one of the key factors in economic reform, namely how to create quality human resources who have skills and highly competitive in global competition. Humans always develop actively and dominantly in every organization's activities, because humans become planners, actors, and determinants of the realization of organizational goals. This study aims to determine the effect of leadership and motivation on employee performance at the South Tangerang Fire and Rescue Service. The method used was explanatory research with a sample of 55 respondents. The analysis technique uses statistical analysis with regression testing, correlation, determination, and hypothesis testing. The results of this study leadership have a significant effect on employee performance by 48.9%, the hypothesis test obtained significance 0,000 <0.05. Motivation has a significant effect on employee performance by 34.8%, hypothesis testing obtained significance 0,000 <0.05. Simultaneous leadership and motivation significantly influence employee performance by 56.8%, hypothesis testing obtained significance 0,000 <0.05.